Morphometry and sedimentation of Kupinde lake and its watershed in Salyan District, Nepal - Sudeep Thakuri; Adhikari, Madhav; Acharya, Pushpa Raj; Shahi, Poshan; Shahi, Raj Kumar (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
Kupinde Lake (elevation: 1,160 m; area: 0.25 km2) is a mid-hill lake located in the Salyan district of Nepal. It serves as an important source of water for the surrounding regions and downstream communities. This study examines the lake morphometry watershed dynamics and sedimentation in Kupinde Lake. A bathymetric survey was conducted using a depth sounder in 2023. The results show that the lake has a maximum depth of 37 m with a total volume of 6.14 million m3. Within the watershed, between 2009 and 2024, forest cover declined by 6.2%, barren land expanded by 60.5%, agricultural land increased by 1.2% and water bodies enlarged by 17.4%. Annual soil loss was estimated at 36,821 t yr-1 (equivalent to 25,394 m3 yr-1), with the highest contributions originating from agricultural land and barren areas, while forested zones exhibited the lowest erosion rates. Over time, soil erosion from agricultural and barren lands has accelerated sedimentation, contributing to gradual lake infilling and altering its morphology. These changes can affect habitat availability, nutrient cycling and water quality, underlining the importance of continuous monitoring and integrated watershed management to mitigate erosion, sustain water resources and preserve ecosystem integrity. This study provides essential baseline data for the conservation and management of Kupinde lake under growing anthropogenic and climatic.